1968
DOI: 10.1246/bcsj.41.684
|View full text |Cite
|
Sign up to set email alerts
|

Organic Catalysts. IV. The Role of the Iron as an Oxidation Catalyst in Copper-Iron-Polyphthalocyanine

Abstract: The role of the iron in copper-iron-polyphthalocyanine in the catalytic action in the oxidation of acetaldehyde ethylene acetal and cyclohexene was investigated on the basis of the inhibition of the reaction by the treatment of copper-iron-polyphthalocyanine with iron-binding agents and oxidizing agents. The catalytic action of copper-iron-polyphthalocyanine decreased or disappeared upon the addition of 2-phenylimidazole and pyridine to the reaction system, and upon the treatment with bromine or concentrated h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

1969
1969
2012
2012

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(1 citation statement)
references
References 3 publications
0
1
0
Order By: Relevance
“…Therefore, the catalysis of binuclear metal phthalocyanines has become a focal point of research work. 16,17 In resent years, our research group has studied the impact of mononuclear transition metal phthalocyanines to Li/SOCl 2 battery. [18][19][20][21][22] It is found that when the transition metal phthalocyanines are added to the electrolyte of the battery, the discharge capability of the battery is improved obviously.…”
mentioning
confidence: 99%
“…Therefore, the catalysis of binuclear metal phthalocyanines has become a focal point of research work. 16,17 In resent years, our research group has studied the impact of mononuclear transition metal phthalocyanines to Li/SOCl 2 battery. [18][19][20][21][22] It is found that when the transition metal phthalocyanines are added to the electrolyte of the battery, the discharge capability of the battery is improved obviously.…”
mentioning
confidence: 99%